Thirteenth workshop on geothermal reservoir engineering: Proceedings - Ramey, H.J., Jr.; Kruger, P.; Horne, R. N.; Brigham, W. E.; Miller, F. G.; Cook, J. W. (Stanford University, 1988)
PREFACE The Thirteenth Workshop on Geothermal Reservoir Engineering was held at Stanford University on January 19-21, 1988. Although 1987 continued to be difficult for the domestic geothermal industry, world-wide activities continued to expand. Two invited presentations on mature geothermal systems were a keynote of the meeting. Malcolm Grant presented a detailed review of Wairakei, New Zealand and highlighted plans for new development. G. Neri summarized experience on flow rate decline and well test analysis in Larderello, Italy. Attendance continued to be high with 128 registered participants. Eight foreign countries were represented: England, France, Iceland, Italy, New Zealand, Japan, Mexico and The Philippines. A discussion of future workshops produced a strong recommendation that the Stanford Workshop program continue for the future. There were forty-one technical presentations at the Workshop. All of these are published as papers in this Proceedings volume. Four technical papers not presented at the Workshop are also published. In addition to these forty five technical presentations or papers, the introductory address was given by Henry J. Ramey, Jr. from the Stanford Geothermal Program. The Workshop Banquet speaker was Gustavo Calderon from the Inter-American Development Bank. We thank him for sharing with the Workshop participants a description of the Bank???s operations in Costa Rica developing alternative energy resources, specifically Geothermal, to improve the country???s economic basis. His talk appears as a paper in the back of this volume. The chairmen of the technical sessions made an important contribution to the workshop. Other than Stanford faculty members they included: J. Combs, G. T. Cole, J. Counsil, A. Drenick, H. Dykstra, K. Goyal, P. Muffler, K. Pruess, and S. K. Sanyal. The Workshop was organized by the Stanford Geothermal Program faculty, staff and students. We would like to thank Marilyn King, Pat Oto, Terri Ramey, Bronwyn Jones, Yasmin Gulamani, and Rosalee Benelli for their valued help with the meeting arrangements and preparing the Proceedings. We also owe great thanks to our students who arranged and operated the audio-visual equipment, especially Jeralyn Luetkehans. The Thirteenth Workshop was supported by the Geothermal Technology Division of the U.S. Department of Energy through Contract No. DE-AS07-84ID12529. We deeply appreciate this continued support. Henry J. Ramey, Jr. Paul Kruger Roland N. Horne William E. Brigham Frank G. Miller Jean W. Cook